How to Reduce Low-Stack Emissions? An Assessment of the Willingness of Residents of Single-Family Houses to Replace Fossil Fuel Heating Systems - Król, Michał; Gomola, Anna (Journal of Public Governance, 2022)
Abstract Objective: The objective of this study is to determine whether occupants of single-family houses in Poland, where low-stack emissions have a particularly negative impact on air quality, are willing to replace their current fossil fuel heating systems. To that end, four research hypotheses were formulated: 1. The majority of households using solid fuel boilers are considering switching to another heat source; 2. Their willingness to replace solid fuel boilers is affected by several statistically significant factors; 3. The main impediment to replacing the heat source is its cost; and 4. The anticipated amount of subsidy is critical in deciding whether or not to purchase a new heat source.Research Design & Methods: These research were considered in the context of data from a CATI survey conducted in July and August 2021 among a representative sample of occupants of single-family houses in Poland. A total of 1007 responses were collected, of which 432 were considered in the subsequent analysis.A literature review, questionnaire results analysis, and a logit regression model were used to verify the hypotheses.Findings: 1. Nearly 80% of respondents would like to replace their heat source, but only 20% are considering ecological heat pumps; 2. People with more knowledge about renewable sources, who are more concerned about the environment and live in older houses, are more likely to replace their heat sources; 3. The high cost of purchasing a new appliance, low subsidies or lack thereof, and the fear of rising bills are the main factors slowing the transition; 4. Higher subsidies increase the number of people willing to replace their heat sources, with the median expecting at least a 50% replacement subsidy regardless of the price of the appliance.Implications/Recommendations: The results of the study can be used by decision makers when formulating and adapting support programs for people replacing old and inefficient solid fuel boilers.Contribution/ Value Added: The research results indicate the issues that have not been formulated in the literature so far, regarding the factors determining the willingness to replace old fossil fuel boilers. The added value of this article is the indication of statistically significant variables such as the age of the house, knowledge about renewable energy and attitude to the environment, which affect the willingness to replace.Article classification: research articleKeywords: Heating transformation, low-stack emissions, single-family houses, preference analysisJEL classification: Q42, Q56, R11